Inserting the imposition of hands - frequencies of brilliance in the health education: experience report of a thematic seminar (Research, Society and Development, 2020)
The study intends to report the experience of inserting the Imposition of Hands – Frequencies of Brilliance in a health training activity. This is a pedagogical didactic report about a Seminar carried out by a curricular activity in community and in society, in the discipline format, offered by the Federal University of Bahia.  The event’s organizing team was composed for teachers, technical-administrative staff and undergraduate enrolled in the first semester of 2019. The Seminar had the participation of 141 people (students, employees of the University and external public) and 8 guests. There were three activities: 1. National (Brazil) and State (Bahia) Policy on Integrative and Complementary Health Practices; 2. Manna - energetic nutritional food of Frequencies of Brilliance; 3. Frequencies of Brilliance - an energy healing system with a theoretical and experiential approach. The Seminar’s experience enabled the understanding of the Frequencies of Brilliance and demonstrated that through integration students can be protagonists in their teaching-learning processes.